2018
DOI: 10.5964/jspp.v6i1.601
|View full text |Cite
|
Sign up to set email alerts
|

One world in diversity – A social-psychological intervention to foster international collective action intention

Abstract: Although effective interventions to increase international collective action for human rights are highly desirable, the validation of theory-based interventions and their transfer to this practical field is still scarce. We investigated whether collective action intention can be improved by using a diversity intervention technique rooted in social psychology. The intervention builds on the ingroup projection model, postulating that negative intergroup relations are based on the perception of ingroups as more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Experimental research has shown a causal link between ingroup perceptions and mental representations of superordinate groups on ingroup projection (Bianchi et al, 2010;Machunsky & Meiser, 2014), but few experiments have examined the link between ingroup projection and intergroup bias. Diversifying perceptions of superordinate group categories does appear to reduce outcomes associated with intergroup bias (Ehrke et al, 2014;Jung et al, 2018;Knab & Steffens, 2018;Mummendey & Wenzel, 1999;Wenzel et al, 2016). However, diversifying perceptions of the superordinate group can also backfire and increase bias due to identity threats (Steffens et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental research has shown a causal link between ingroup perceptions and mental representations of superordinate groups on ingroup projection (Bianchi et al, 2010;Machunsky & Meiser, 2014), but few experiments have examined the link between ingroup projection and intergroup bias. Diversifying perceptions of superordinate group categories does appear to reduce outcomes associated with intergroup bias (Ehrke et al, 2014;Jung et al, 2018;Knab & Steffens, 2018;Mummendey & Wenzel, 1999;Wenzel et al, 2016). However, diversifying perceptions of the superordinate group can also backfire and increase bias due to identity threats (Steffens et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the literature on identity threat, when the position of one’s group within the superordinate category is challenged, projection can take the form of a defensive action (Rosa & Waldzus, 2012). More recently, even some of the classic suggestions for improving intergroup attitudes from the social identity and ingroup projection literature, such as superordinate group complexity (Knab & Steffens, 2018), have been found to induce threat for certain groups under certain conditions (Steffens et al, 2017). Furthermore, threats to the stability of either the subordinate or superordinate identity appear to evoke attempts to restore stability on various levels of identity, thereby illustrating the interconnections between subordinate and superordinate identities (Jung et el., 2018).…”
Section: The Ingroup Projection Modelmentioning
confidence: 99%